Golden Years of Australian Radio Astronomy An Illustrated History - Orchiston, Wayne (Historical & Cultural Astronomy, 2021)
The evolution of Australian radio astronomy from 1945 to 1960 has been studied in detail by numerous historians of science in recent years. This Open Access book is the first to present an overview of this remarkable chapter in Australian science. The book begins in the post-war period, as the Radiophysics Laboratory in Sydney switched from secret wartime research on radar to peacetime applications of this new technology. Next follows the detection of radio waves from space and the ensuing transformation of this fledgling science into the dominant research program at the Radiophysics Lab. Drawing from this history, the book shows how by 1960 the Radiophysics Lab had become the largest and most successful radio astronomy group in the world. The final chapter presents an overview of Australian radio astronomy from 1960 to the present day, as Australia prepares to co-host the multi-national, multi-billion-dollar Square Kilometre Array. Nearly 300 high-quality images complement the text, drawn from a wide range of sources including the extensive collection held by the CSIRO Radio Astronomy Image Archive. The book will be an essential reference for readers interested in the scientific and cultural development of radio astronomy. This book is published open access under a CC BY 4.0 license.